Anomalous bottom topography of a small lake in the Larsemann Hills Oasis (East Antarctica) - S. Grigorieva D.; M. Kuznetsova R.; M. Shitov V.; G. Priakhina V.; M. Kashkevich P.; С. Григорьева Д.; М. Кузнецова Р.; М. Шитов В.; Г. Пряхина В.; М. Кашкевич П. (IGRAS, 2022)
Results of studying the bottom relief of a unique small reservoir (lake) located in the south of the Broknes peninsula, the oasis of the Larsemann Hills (East Antarctica) are presented. The ﬁrst reliable depth measurements carried out in January 2022 demonstrated that within the shallow basin of the lake (average depth of 1 m or less) there are four narrow depressions (canyons) with a width of 5.5 m or less and a depth reaching 27.7m. Such a character of bottom relief has not been found before in any of the more than 150 known lakes of this oasis. To study this phenomenon, we performed ﬁeldwork including hydrological observations, measurements of water temperature and mineralization at diﬀerent horizons, high-precision bathymetric survey, and the underwater photography together with geological and geophysical investigations of the lake bank slope. A working hypothesis explaining the origin of such unusual bottom relief suggests a version of frost cracking that propagates along the fracture zone in the bedrock followed by the formation of cryoeluvium and the removal ﬁne-grained particles (suﬀusion). В результате полевых работ 2021/22 г. в оазисе Холмы Ларсеманн (Восточная Антарктида) описан малый водоём с уникальными для данного региона морфометрическими характеристиками. При размерах 143 × 53 м и средней глубине большей части котловины около 1 м в его котловине развиты четыре узких впадины, ширина которых не превышает 5,5 м, а глубина достигает 27,7 м. Приведены результаты гидрологических работ на этом озере, геолого-геофизического обследования его котловины, а также предварительная гипотеза о механизме его формирования.